Literasi Keuangan Berbasis Digital untuk Siswa SMP Al-Azhar 25 Tangerang Selatan - AKHSANI, NOVI; wiwit Setyawati; Nurbaeti (Universitas Pamulang, 2025)
In the digital era, financial literacy skills are essential skills that must be possessed from an early age. Many junior high school students, including those at SMP Al-Azhar 25 Tangerang Selatan, do not yet have an adequate understanding of money management, savings, simple investments, and the risks of using digital platforms related to finance. This gap can have a long-term impact on their financial behavior in the future. This community service aims to improve students' understanding and awareness of digital-based financial literacy through an interactive and contextual approach, which is in accordance with the needs of junior high school-aged adolescents. The method used in this program is a digital-based educational approach via zoom. Activities are carried out in the form of interactive seminars, simulations of the use of digital financial applications (money trackers), and quizzes to measure understanding. Evaluation is carried out by comparing the results of the pre-test and post-test. The results show an increase in understanding of financial literacy based on pre-test and post-test scores. Students showed high enthusiasm for the digital budgeting simulation and were able to better identify digital financial risks after the activity. This community service activity has proven effective in improving the digital financial literacy of junior high school students. An interactive approach and the use of technology are the keys to success in attracting student interest and understanding. This program can be replicated in other schools as a contextual and sustainable financial literacy education model. Keywords: financial literacy; money tracker; digital